Identification of transarterial chemoembolization candidates in advanced hepatocellular carcinoma patients classified solely by performance status 1: a multicenter retrospective study - Jing Li; Zhexuan Wang; Litian Ma; Jiakun Gou; Yunan Feng; Yanju Lou; Luo Zuo; Tao Wang; Yong Liang; Yongchao Zhang; Enxin Wang; Yang Bai (Scientific Reports)
Abstract The Barcelona Clinic Liver Cancer (BCLC) advanced stage of hepatocellular carcinoma (HCC) includes a heterogeneous population, and new patient-tailored therapeutic indications are needed. Emerging evidence suggest that patients in this stage with mild tumor-related symptoms may benefit from more aggressive treatments including transarterial chemoembolization (TACE) and obtain better outcomes. This study aimed to investigate the effects of TACE on HCC patients with mild tumor-related symptoms and risk-stratify them for selecting potential candidates for TACE. We retrospectively collected data from 745 patients with liver-confined HCC undergoing TACE at 15 different centers from January 2015 to November 2022. The prognostic abilities of performance status (PS score of 0 vs. 1) were separately evaluated in high- and low-risk groups using the Hepatoma Arterial-embolization Prognostic (HAP) scoring model and its variants. PS1 remained an independent prognostic factor for overall survival (OS) in the whole cohort (P = 0.035). Interestingly, it lost its prognostic value for patients in low-risk groups (grade A + B) in all the four HAP models. This population with PS1 alone achieved similar OS to their counterparts with PS0. Risk stratification based on HAP scoring models could discriminate potential candidates from HCC patients in BCLC-C stage with PS1 alone. These patients could be classified into BCLC-B stage and benefit from TACE treatment.